Legal liability of Multimodal Transport Operators for cargo loss and damage arising from armed conflict in the Strait of Hormuz: Legal liability of Multimodal Transport Operators for cargo loss and damage arising from armed conflict in the Strait of Hormuz - Pitriyani Pitriyani; Nuchraha Alhuda Hasnda Nuchraha Alhuda Hasnda (Privietlab, 2026)
The growth of international trade has driven an increase in the use of multimodal transport systems, which allow goods to be shipped via two or more modes of transport under a single contract. In this system, the Multimodal Transport Operator bears full responsibility for the entire shipping process; however, the absence of a uniform international legal regime means that the determination of its libility still depends on the conventions of each mode transport, which have varying standards. This issue becomes even more complex when transportation takes place amid conflict situations, such as in the Strait Hormuz since February 2026. This study employs a normative legal approach to examine the MTO’s liability for loss and damage, as well as the scope of applicability of war risk clauses in such contexts. The findings indicate that the MTO’s liability does not automatically lapse in conflict situations, as liability exemptions still require cumulative proof of force majeure and compliance with due diligence standard. Nor can the war risk clause be applied absolutely, given that its applicability is limited by the contract’s terms, the principle of presumed liability; the presence or absence of negligence, and whether the resulting loss is direct or indirect. The absence of a unified international legal framework remains a serious gap, particulary when losses cannot be localized to a specific segment of transportation.